The Carrier Rate of Extended Spectrum Beta Lactamase (ESBL) Producing Bacteria in Cockroaches (Periplaneta americana) in Hospital and Community - Puspita, Ardhiya; Arizandy, Radita Yuniar; Wasito, Eddy Bagus; , Kuntaman (Folia Medica Indonesiana, 2021)
Highlight:• Bacteriologically for colonization of ESBL producing Enterobacteriaceae in cockroaches (Periplaneta americana) were analyzed. • The prevalence of ESBL producing bacteria among cockroaches in hospitals is bigger than in households. Abstract: Cockroach (Periplaneta americana) is one of the vectors in the environment that can transmit disease. Cockroaches can act as potential mechanical vectors of antibiotic resistant bacteria. Enterobacteriaceae is a gram-negative bacteria that has natural habitats in the digestive tract of humans and animals. Enterobacteriaceae that produce Extended Spectrum β-lactamases (ESBLs) have emerged as major pathogens in hospitals. The study analyzed the prevalence of ESBL producing bacteria in cockroaches that lived in hospitals and residential homes. In this study, a total of 200 cockroaches consisting of 100 cockroaches from the hospital environment and 100 cockroaches from the residential environment were analyzed bacteriologically for colonization of ESBL producing Enterobacteriaceae. The specimen of the alimentary tract was taken and sub-cultured in MacConkey agar supplemented with cefotaxime 2 ug/ml. Growth colonies were suggested as an ESBL-producing bacteria, then were confirmed as ESBL producers by the Double Disk Synergy Test (DDST). The ESBL gene was detected by Polymerase Chain Reaction (PCR). Among 100 household cockroach samples, 14 (14%) were identified as ESBL producers, while 100 hospital cockroaches were 26 (26%) positive ESBL. The ESBL gene, in hospital cockroach were identified of CTXM 19 (19%), SHV 7 (7%), and not any TEM gene, while among household cockroaches were identified CTXM 2 (2%), SHV 11 (11%), and also not detected TEM ESBL gene. Among ESBL genes, only the CTXM gene was significantly different between household and hospital cockroaches.